Effects of health training in knowledge and surgical wound management - Eka Yudha Chrisanto; Nur Afni (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: The surgery in Indonesia ranks 11th out of 50 treatments for disease patterns in hospitals in Indonesia, which is an estimated 32% of them were laparotomy. The number of abdominal surgical cases in Lampung Province in 2017 was (28.95%) and increased in 2018 by (32.45%).Purpose: Know the effect of health training in knowledge and surgical wound management.Methods: This type of study was quantitative, with the Pre-Experiment design and the design one group pre test - post test. The populations were all of postoperative patients and samples of 34 people with a total sampling technique. Data collection uses questionnaire sheets and the statistical test used dependent t-test.Results: The average knowledge about postoperative wound care before being given health training of 14.18 and a standard deviation of 1.749. The average knowledge about postoperative wound care after being given health training of 17.06 and a standard deviation of 3.142, with p-value = (0,000 <0,05).Conclusion: There was the effect of health training in knowledge and surgical wound management. Health workers are expected to be able to apply the provision of health training to postoperative patients to improve patient knowledge in subsequent care and be used as a reference for making policies regarding the provision of health training to postoperative patients.